2003
DOI: 10.1111/j.1365-2338.2003.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the potential development of Diaporthe helianthi epidemics in Italy*

Abstract: Diaporthe helianthi is the causal agent of a severe sunflower disease but, in Italy, disease outbreaks are sporadic with no significant losses. The present work investigates the role of meteorological conditions on the potential development of D. helianthi epidemics in Italy, using the French model Asphodel, which simulates the effect of air temperature, relative humidity and rainfall on ascospore maturation and dispersal, infection establishment, disease onset and severity during the period of host susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…Yield reductions of up to 40 % have been recorded in Europe (Masirevic & Gulya 1992) including the former Yugoslavia as well as France where it was considered a major pathogen of sunflower (Battilani et al 2003, Debaeke et al 2003). Diaporthe helianthi is also widespread in the sunflower growing regions of the USA (Gulya et al 1997) but has not been reported from Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Yield reductions of up to 40 % have been recorded in Europe (Masirevic & Gulya 1992) including the former Yugoslavia as well as France where it was considered a major pathogen of sunflower (Battilani et al 2003, Debaeke et al 2003). Diaporthe helianthi is also widespread in the sunflower growing regions of the USA (Gulya et al 1997) but has not been reported from Australia.…”
Section: Introductionmentioning
confidence: 99%
“…The economic losses for sunflower cultures caused in Europe by the pathogen Diaporthe helianthi, first recorded in the former Yugoslavia [19], induced several research groups in the afflicted countries to conduct studies on that system. First epidemiological analysis revealed different incidence levels of the disease, the stem canker, which occurred on the host based on geographic location: heavy damages were reported in the former Yugoslavia [42] and in France [21], whereas in Italy the pathogen is only sporadically found, in spite of conducive climatic conditions [24,43]. Previous investigations were aimed at D. helianthi intraspecific variability and were based on morpho-physiological, biological and genetic characters [26,27], host cultivars/pathogen isolates interaction [28], molecular genotypic and phenotypic features [29].…”
Section: Discussionmentioning
confidence: 99%
“…Heavy yield losses have been reported in France and in the former Yugoslavia, where environmental conditions are conducive to infection [21,22]. In Italy, the disease was first recorded in 1987 [23], but since then the pathogen has appeared only sporadically and does not cause significant yield losses, despite the fact that climatic conditions are conducive to an epidemic outbreak of the disease [24]. The lack of such epidemics in Italy may be due to different pathogen populations occurring in the country.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more simulation models have been developed, e.g. for the simulation of ascospores of Venturia inaequalis on apple trees (Rossi et al ., 2003a), for the risk of Fusarium head blight in wheat (Rossi et al ., 2003b), and for estimating the potential development of Diaporthe helianthi epidemics (Battilani et al ., 2003).…”
Section: Important National Developments Of Decision Support Systemsmentioning
confidence: 99%